On the bromination of aromatics, alkenes and alkynes using alkylammonium bromide: Towards the mimic of bromoperoxidases reactivity. Issue 50 (14th December 2016) - Mendoza, Fabian; Ruíz-Guerrero, Rosario; Hernández-Fuentes, Carlos; Molina, Paulina; Norzagaray-Campos, Mariano; Reguera, Edilso
Graphical abstract: Highlights: Efficient bromination method of aromatic substrates with NH4 VO3 /H2 O2 in mild reaction conditions. Bromination of electron-rich aromatics with TBAB as bromine source. VO(O2 ) + is the vanadium specie that promotes the bromination of organic substrates. Abstract: This article describes an efficient method of bromination of organic substrates including aromatics, alkenes and alkynes with NH4 VO3 as a catalyst and H2 O2 as an oxidant agent using a non-toxic and easy-to-handle source of bromine, tetrabutylammonium bromide. The process was developed under mild reaction conditions and is an innovation from reported methods in aspects such as: i ) short reaction times, ii ) the ability to work at room temperature, iii ) regioselectivity and good yields.